GAYA BAHASA LIRIK LAGU DALAM ALBUM LINTASAN WAKTU KARYA KARYA DANILLA RIYADI: KAJIAN STILISTIKA - Riadi, Gregorius Octa; Priyadi, A. Totok; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractWriterâ€™s background to observe the style of language is to find better understanding about the style of the language itself. The purpose of this research is to describe meanings and style of language of the lyrics in Lintasan Waktu album by Danilla Riyadi. The method in this research is using Descriptive Method, Qualitative Research Approach, and Library Research. Data in this research is style of language in the lyrics of Lintasan Waktu album by Danilla Riyadi. Data sources of this research is the entire songs in Lintasan Waktu album by Danilla Riyadi amount to 10 (ten) songs. The results of this research in observing the style of language in every-lyric of songs of Lintasan Waktu album by Danilla Riyadi, Writer founds that 8 (eight) styles of language according to scope of problem in this research that is rhetorical style of language are: Alliteration, Asyndeton, Polysyndeton,Â Assonance, Litotes, Hyperbola; and Figurative style of language: Personification and Symploce. In this research, writer founds that 7 (seven) meanings contain in the lyrics of the songs of Lintasan Waktu album by Danilla Riyadi (Extension, Gereflecter, Grammatical, Non-referential, Cognitive, Figurative, and Pictorial). Keywords : The Style of Language, Meaning